2022
DOI: 10.1002/srin.202200479
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Microstructure with Anisotropy of Low‐Temperature Toughness in Two API X70 Pipeline Steels

Abstract: This study aims to investigate the correlation between the microstructures and the anisotropy of low-temperature toughness for two high-strength API X70 pipeline steels fabricated at different coiling temperatures. The microstructures are characterized using an optical microscope, a scanning electron microscope, and an electron backscattered diffraction analysis, with tensile and Charpy V-notch impact tests also conducted on the steel specimens in various directions relative to the rolling direction. Some pear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Owing to a decrease in the rolling start and end temperatures, the volume fractions of PF and aF increased, and the grain size decreased. Previous studies [26,27] reported that PF and aF had fine grains with high-angle grain boundaries (HagBs, >15°), whereas gB and BF exhibited relatively coarse grains with high fractions of the low-angle grain boundaries (lagBs, 5° ~ 15°). Regarding the fraction of the misorientation Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Owing to a decrease in the rolling start and end temperatures, the volume fractions of PF and aF increased, and the grain size decreased. Previous studies [26,27] reported that PF and aF had fine grains with high-angle grain boundaries (HagBs, >15°), whereas gB and BF exhibited relatively coarse grains with high fractions of the low-angle grain boundaries (lagBs, 5° ~ 15°). Regarding the fraction of the misorientation Fig.…”
Section: Resultsmentioning
confidence: 95%
“…However, the DQT steel showed unsatisfactory low-temperature toughness despite having finer effective grains than the DQ steel because the hard cementite in it served as a crack initiation site. Several researchers reported that precipitated cementite in the ferrite matrix became the initiation site for microcracks when the stress increased, and then these cracks propagated through the ferrite {100} plane [44,45]. Therefore, it can be concluded that tempering process adversely affects low-temperature toughness because the formation of cementite during tempering accelerates crack initiation.…”
Section: Ductile-to-brittle Transition Behavior and Low-temperature T...mentioning
confidence: 99%